2006
DOI: 10.1079/phn2005879
|View full text |Cite
|
Sign up to set email alerts
|

Television advertising and children: lessons from policy development

Abstract: Aim: To conduct a policy review of the regulations related to food advertising on television aimed at children. Design: The study consisted of documentary analysis of relevant legislation and policy documents related to children's advertising from both industry and nongovernmental organisations at a global level and in 20 countries. This was supported with semi-structured telephone interviews with individuals from 11 countries. Results: The initial findings resulted in a listing of regulatory impacts from whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 6 publications
1
56
0
1
Order By: Relevance
“…The effectiveness of efforts to stimulate industry self-regulation is also uncertain. Caraher et al (36) found large differences in the enforcement and monitoring of self-regulation in twenty countries and a lack of representation of public health and consumer groups on industry self-regulating bodies. Control and regulation can be implemented regionally, as some states in Australia are considering, but preferably need to be addressed at the national or international level.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…The effectiveness of efforts to stimulate industry self-regulation is also uncertain. Caraher et al (36) found large differences in the enforcement and monitoring of self-regulation in twenty countries and a lack of representation of public health and consumer groups on industry self-regulating bodies. Control and regulation can be implemented regionally, as some states in Australia are considering, but preferably need to be addressed at the national or international level.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…An international study conducted in 1996 on television food advertising patterns indicated that Australia, the USA and the UK had the highest proportion of overall food advertisements, with 83, 98 and 79% of these food adverts, respectively, for sweet/fatty foods 9 . The question of whether food advertising to children should be more strongly regulated has been raised in several countries 13 . Children less than 8 years of age, in particular, are thought to lack the cognitive skills required to recognise an advertiser's persuasive intent and purpose 4,14 , and are therefore more at risk of commercial exploitation.…”
mentioning
confidence: 99%
“…Government policymakers generally had a low profile, until a policy window appeared when they swiftly revealed their preference for government intervention. Overall, it was difficult to determine the nature and extent of covert advocacy, particularly by the food industry, which is well known for such tactics in other countries [18,[53][54][55]. A request under the Official Information Act produced internal government documents.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on how cogently industry has presented its views governments internationally have produced varied policies on television advertising to children. These range from complete bans as occurs in Sweden and Norway, to prohibitions in the United Kingdom on food and drink advertisements for less healthy food during children's viewing times [17], to total self regulation by the food and advertising industries in the United States and New Zealand [18]. In both these countries, industry funded institutions administer voluntary guidelines for the quantity and content of advertisements targeting children [8,19].…”
Section: Introductionmentioning
confidence: 99%